2017
DOI: 10.4172/pharmaceutical-sciences.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Cetirizine Dihydrochloride, beta-Cyclodextrin Inclusion Complex by Ethanol Kneading for Taste Masking

Abstract: Katewongsa, et al.: Cetirizine Dihydrochloride and β-Cyclodextrin Complex by Ethanol KneadingCetirizine dihydrochloride has a very unpleasant bitter taste. To mask the bitter taste, complexation with β-cyclodextrin using ethanol as a kneading solvent was investigated and evaluated by Fourier transform infrared spectroscopy, differential scanning calorimetry, powder X-ray diffractometry, thermogravimetric analysis, simultaneous X-ray diffractometry-differential scanning calorimetry measurement and 1 H-nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The DSC thermogram of blank hydrogels showed a melting peak of IA at approximately 160°C ( Figure 6 ) as reported previously ( Kirimura et al, 2011 ) and poly (acrylamide) above 300°C. Pure CTZ HCl exhibited a melting peak at approximately 201.3°C, followed by a degradation peak at approximately 220°C and is in agreement with previous studies ( Katewongsa et al, 2017 ; Afzal et al, 2018 ). CTZ HCl peaks diminished in drug-loaded hydrogels (F5) indicating dispersion of the drug in an amorphous form.…”
Section: Resultssupporting
confidence: 93%
“…The DSC thermogram of blank hydrogels showed a melting peak of IA at approximately 160°C ( Figure 6 ) as reported previously ( Kirimura et al, 2011 ) and poly (acrylamide) above 300°C. Pure CTZ HCl exhibited a melting peak at approximately 201.3°C, followed by a degradation peak at approximately 220°C and is in agreement with previous studies ( Katewongsa et al, 2017 ; Afzal et al, 2018 ). CTZ HCl peaks diminished in drug-loaded hydrogels (F5) indicating dispersion of the drug in an amorphous form.…”
Section: Resultssupporting
confidence: 93%
“…FTIR, DSC, PXRD, 1 H MR, [75] Cetirizine dihydrochloride α-, β-, and γ-cyclodextrin No detailed information provided. FTIR, UV-VIS, HPLC [76] Cetirizine dihydrochloride α-, β-, and γ-cyclodextrin…”
Section: Cetirizine Dihydrochloride β-Cyclodextrinmentioning
confidence: 99%
“…In [84], the authors showed how arundic acid Even in the form of physical mixture with API, β-CD exhibits some taste-masking properties that are greatly improved when the complex is being administrated. Adapted from [75], licensed under CC BY 3.0 (Creative Commons Attribution License 3.0).…”
Section: Othersmentioning
confidence: 99%
“…The pure drug, polymer mix and formulation were subjected to Fourier transform infrared (FTIR) studies. The pure drug, polymer and formulation was mixed with small quantity of IR grade potassium bromide and scanned in the range of 4000-400 cm −1 using an FTIR JASCO instrument (Jasco Corporation, Tokyo, Japan) [8].…”
Section: Compatibility Studiesmentioning
confidence: 99%